2016
DOI: 10.1128/jvi.02669-15
|View full text |Cite
|
Sign up to set email alerts
|

Broad Anti-Hepatitis C Virus (HCV) Antibody Responses Are Associated with Improved Clinical Disease Parameters in Chronic HCV Infection

Abstract: During hepatitis C virus (HCV) infection, broadly neutralizing antibody (bNAb) responses targeting E1E2 envelope glycopro-teins are generated in many individuals. It is unclear if these antibodies play a protective or a pathogenic role during chronic infection. In this study, we investigated whether bNAb responses in individuals with chronic infection were associated with differences in clinical presentation. Patient-derived purified serum IgG was used to assess the breadth of HCV E1E2 binding and the neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…Our work supports prior more limited studies showing that HCVcc and HCVpp with identical E1E2 have similar relative neutralization resistance (Bailey et al, 2015a;Fofana et al, 2012;Swann et al, 2016;Urbanowicz et al, 2015). Importantly, to our knowledge, this is the first study to show this correlation using a diverse panel of human bNAbs targeting distinct epitopes across E1E2 and a large panel of diverse natural E1E2 variants, suggesting that these results are broadly applicable to other E1E2 variants and other antibodies.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our work supports prior more limited studies showing that HCVcc and HCVpp with identical E1E2 have similar relative neutralization resistance (Bailey et al, 2015a;Fofana et al, 2012;Swann et al, 2016;Urbanowicz et al, 2015). Importantly, to our knowledge, this is the first study to show this correlation using a diverse panel of human bNAbs targeting distinct epitopes across E1E2 and a large panel of diverse natural E1E2 variants, suggesting that these results are broadly applicable to other E1E2 variants and other antibodies.…”
Section: Discussionsupporting
confidence: 75%
“…Neutralization results obtained using HCVcc and HCVpp have generally been similar (Fofana et al, 2012;Meunier et al, 2005;Scheel et al, 2008;Swann et al, 2016;Urbanowicz et al, 2015), but comparisons of specific infectivity and neutralization of HCVpp and HCVcc expressing genetically identical E1E2 variants have previously been performed only on a fairly limited basis, and to our knowledge neutralization of E1E2-matched HCVpp and HCVcc has never been compared using a diverse panel of bNAbs targeting distinct epitopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of neutralizing antibodies in HCV suppression in vivo was not well understood . It has been reported that antibodies against HCV E2 exerted a protective effect against HCV and contributed to virus clearance . In this study, both the serum E2 antibody level and the HCV neutralizing activity increased with HCV RNA load.…”
Section: Discussionsupporting
confidence: 87%
“…These particles have been produced with a variety of E1E2 variants from multiple isolates and genotypes [15]. Diverse HCVpp panels have been used to define neutralizing breadth of antibodies and to show that development of broadly neutralizing antibodies is associated with spontaneous clearance of HCV infection [10, 11], and reduced liver fibrosis in chronic infection [16]. …”
Section: Introductionmentioning
confidence: 99%